Far-infrared emission in luminous quasars accompanied by nuclear outflows - Maddox, Natasha; Jarvis, M.J.; Banerji, M.; Hewett, P.C.; Bourne, N.; Dunne, L.; Dye, S.; Eales, S.; Furlanetto, C.; Maddox, S.J.; Smith, M.W.L.; Valiante, E. (Oxford University Press, 2017)
Combining large-area optical quasar surveys with the new far-infrared (FIR) Herschel-ATLAS Data Release 1, we search for an observational signature associated with the minority of quasars possessing bright FIR luminosities. We find that FIR-bright quasars show broad C IV emission-line blueshifts in excess of that expected from the optical luminosity alone, indicating particularly powerful nuclear outflows. The quasars show no signs of having redder optical colours than the general ensemble of optically selected quasars, ruling out differences in line-of-sight dust within the host galaxies. We postulate that these objects may be caught in a special evolutionary phase, with unobscured, high black hole accretion rates and correspondingly strong nuclear outflows. The high FIR emission found in these objects is then either a result of star formation related to the outflow, or is due to dust within the host galaxy illuminated by the quasar. We are thus directly witnessing coincident small-scale nuclear processes and galaxy-wide activity, commonly invoked in galaxy simulations that rely on feedback from quasars to influence galaxy evolution.